2022
DOI: 10.1186/s42358-022-00237-4
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS): a Brazilian cohort

Abstract: Background Paediatric inflammatory multisystem syndrome (PIMS) associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been described since mid-April 2020 with the first reports coming from Europe. Our objective was to describe the characteristics of patients among the Brazilian population. Methods A multicenter retrospective study was conducted with the participation of five pediatric rheumatology centers in Brazil during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…In two different meta-analysis involving in total 1,700 MIS-C cases ( 3 , 23 ) gastrointestinal symptoms occurred in 71% and 87% of the patients, and abnormal echocardiogram/myocardial dysfunction in 59% and 55% of the cases. Concerning other demographic and clinical characteristics of our national cohort, findings are also comparable to other published cohorts with most affected children being previously healthy ( 2 , 5 , 15 ), developing high rate of cardiac complications but evolving favourably in most of the cases with relatively short hospital stay (<10 days) ( 1 , 5 , 14 , 15 ,). With prompt diagnosis and treatment, 100% of our patients had an excellent evolution with no permanent organ failure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In two different meta-analysis involving in total 1,700 MIS-C cases ( 3 , 23 ) gastrointestinal symptoms occurred in 71% and 87% of the patients, and abnormal echocardiogram/myocardial dysfunction in 59% and 55% of the cases. Concerning other demographic and clinical characteristics of our national cohort, findings are also comparable to other published cohorts with most affected children being previously healthy ( 2 , 5 , 15 ), developing high rate of cardiac complications but evolving favourably in most of the cases with relatively short hospital stay (<10 days) ( 1 , 5 , 14 , 15 ,). With prompt diagnosis and treatment, 100% of our patients had an excellent evolution with no permanent organ failure.…”
Section: Discussionsupporting
confidence: 88%
“…This unusual inflammatory disease has now been reported worldwide. It is manifested by different clinical symptoms like high persisting fever, skin rash, multiple organ involvement and dysfunction including heart failure (3)(4)(5)(6)(7). Since first MIS-C cases were published, different scientific societies [Center for Disease Control and Prevention (CDC), Royal College of Pediatrics and Child Health…] have developed diagnostic criteria and case definitions.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the blood count were most apparent in the presence of lymphopenia and thrombocytopenia in patients with MIS-C [25,26]. There were no significant differences in lymphopenia or thrombocytopenia between groups.…”
Section: Discussionmentioning
confidence: 71%
“…Only few studies found girls to be affected more. 2,3,8,[13][14][15][16][17] Most of the cases recovered. Only 4 (6%) patients died in this study.…”
Section: Discussionmentioning
confidence: 99%